2008
DOI: 10.1007/s12199-008-0026-0
|View full text |Cite
|
Sign up to set email alerts
|

Learning behavior in rat offspring after in utero and lactational exposure to either TCDD or PCB126

Abstract: Objectives We studied and compared the possible effects of in utero and lactational exposure to 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) or 3, 3 0 , 4, 4 0 , 5-pentachlorobiphenyl (PCB126) on learning behavior in offspring. MethodsPregnant Long-Evans Hooded rats were administered either TCDD (50, 200, or 800 ng/kg) or PCB126 (500, 2,000 or 8,000 ng/kg) on gestational day 15. A procedure of schedule-controlled operant behavior was applied to examine learning behavior in the male and female offspring at 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…However, in recent years, such a premise has been challenged by piles of evidence that shows the presence of non-monotonic modes of action of chemicals and hormones in a low-dose range and may elucidate the underlying mechanisms [84]. As the non-monotonic dose-response relationship found in this study was widely consistent among the indices of behavior and immunohistochemistry, the present results strongly suggest that TCDD is a chemical that can induce a non-monotonic dose-response effect on a systemic level, an observation that is consistent with previous studies on rat progeny [14], [19], [20]. To address mental disorders and related health problems as the endpoints of low-dose exposure of TCDD, further studies are required to clarify the non-monotonic association between a low dose of TCDD and its effects on the brain and behavior on both the molecular and systemic levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, in recent years, such a premise has been challenged by piles of evidence that shows the presence of non-monotonic modes of action of chemicals and hormones in a low-dose range and may elucidate the underlying mechanisms [84]. As the non-monotonic dose-response relationship found in this study was widely consistent among the indices of behavior and immunohistochemistry, the present results strongly suggest that TCDD is a chemical that can induce a non-monotonic dose-response effect on a systemic level, an observation that is consistent with previous studies on rat progeny [14], [19], [20]. To address mental disorders and related health problems as the endpoints of low-dose exposure of TCDD, further studies are required to clarify the non-monotonic association between a low dose of TCDD and its effects on the brain and behavior on both the molecular and systemic levels.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical and epidemiological studies have revealed the occurrence of a variety of signs and symptoms in dioxin-exposed human populations, including disturbances in psychomotor and neurobehavioral functions in children [8], [9], [11]. In utero and lactational exposure of rodents to 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD), the most toxic congener among dioxin family, induces abnormal sexually dimorphic behaviors in adulthood [12], [13], [14], [15], [16], [17], and alters learning behaviors [18], [19], [20], [21], [22], [23], [24], [25], [26]. Previous studies have shown that the cerebral cortex is a vulnerable target to TCDD insult.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the TCDD dose is low and administered to pregnant dams, nearly all of the dioxin is eliminated from the body of the offspring at the time of analysis (Gasiewicz et al, 1983), with no overt signs of toxicity. It is interesting to note that different laboratories have also reported alterations in the higher brain functions of TCDDexposed rats and mice under such exposure conditions (Markowski et al, 2002;Widholm et al, 2003;Nishijo et al, 2007;Hojo et al, 2008). However, the mechanism of TCDDinduced neurotoxicity remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of several endocrine disruptors to rats at 5 days of age also causes motor hyperactivity at 4-5 weeks of age, concomitant with a decrease in the gene expression of dopamine transporter DAT1 (Ishido et al, 2005). Fetal exposure to TCDD results in hyperactivity in rats (Hojo et al, 2008;Nishijo et al, 2007). Although the extracellular dopamine concentration and expression level of the dopamine transporters were not analyzed in the present study, our transgenic mice treated with TCDD may also have shown motor hyperactivity owing to an increment of dopaminergic input in the mesotelencephalic system arising from the enhanced expression of TH and increased number of TH-ir neurons.…”
Section: A)mentioning
confidence: 99%
“…In fact, epidemiological data have suggested that the serum concentration of dioxins and related compounds in children are associated with the likelihood of developing LD and ADD (Lee et al ., ). In agreement with these epidemiological findings, previous experimental studies have indicated that hyperactivity occur subsequent to fetal and lactational exposure to TCDD (Hojo et al ., ; Nishijo et al ., ).…”
Section: Introductionmentioning
confidence: 97%